Effect of sodium fluoride addition as a disinfectant on some properties of alginate impression material - Alaa M Hussian; Raghdaa k Jassim (College of Dentistry/ University of Baghdad, 2015)
Background: Impression materials, impression trays, and poured stone cast have been said to be the main source of cross infection between patients and dentists. However, it was observed that disinfection of the impression is not performed systematically in routine dental practice. Disinfection of alginates either by immersion or spray technique was found to cause dimensional inaccuracies, although with proper disinfection of alginates there were small dimensional changes. A variety of fluoride releasing products designed for topical use is currently available. Following their use, varied amount of fluoride is systemically absorbed depending on the fluoride concentration and the manner of its use. The objective of this study was to evaluate the effect of addition (0%, 0.25%,0.5%,1%, 2%, 3%, 4% ) of (NaF) as a self-disinfection to alginate impression material powder and its effect on setting time, tear strength, dimensional change and accuracy of alginate impression materials. Materials and methods: A total No. of (700) specimen were used in this study.These specimens were divided into (5) main groups according to the tests used. Each of the four main groups contain (70) specimen divided into 7 subgroups (ten specimens to be tested for each (7)concentrations which is composed of six percentages of NaFwith alginate powder (0.25%,0.5%,1%, 2%, 3%, 4% )and one for control (0% NaF) , while the fifth group (Microbiological test) contain 420 specimen were divided between Streptococcus mutans and Candida albicans as (120) specimen for each one that was subdivided into three subgroups (specimens taken before impression casting, specimensafter pouring of alginate with stone andspecimens of stone were taken from the casts) in which it contain the same subgroups of the other concentrationsof (NaF) to test its efficacy against (Streptococcus mutans and Candida albicans). Results: Tear strength for all experimental impression materials was greater than those of the control products. There were no statistically significant differences between the dimensional change tests and also reproduction of detail test.With regard to setting time of the impressions, statisticallyreduction were seen between the control and experimental groups of alginate impression materials that contain (NaF). Self-disinfection of alginate impression material containing NaF showed a significant reduction in the count of cell forming unit of microorganisms immediately after impressions were made. Conclusion: In cooperation of specific concentrations of (NaF) as a disinfectant in alginate dental impression produced a significant reduction of contamination, also they caused non-significant effect on dimensional stability, detail reproduction and significant increase in tear strength. Therefore it is recommended as step in preventing cross contamination. Keywords: Alginate, NaF, Candida Albicans, streptococcus mutans.